Pengembangan Karakter Siswa SDS 118 Muhammadiyah Gunung Tua melalui Pembelajaran PAI Berbasis Nilai-Nilai Islam - Azizah, Nur; Annisa Nabila; Anggi Julianti; Putri Fadillah; Sangkot Anisa; Maya Sari; Padilah Hasibuan; Rani Ismil Hakim (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to describe the development of students' character at SD Swasta 118 Muhammadiyah Gunung Tua through Islamic Religious Education (PAI) learning based on Islamic values. Islamic Religious Education plays a strategic role in instilling religious values from an early age, especially at the elementary school level. Through worship habituation strategies, teacher role modeling, contextual learning, and the integration of Islamic values into school culture, students' character can be comprehensively developed encompassing spiritual, moral, and social aspects. This research uses a qualitative descriptive approach with research subjects including the principal, PAI teachers, and students. The results show that the implementation of Islamic values-based PAI learning has a positive impact on the formation of students' religious character, reflected in worship discipline, respectful attitudes, prayer habits, social care, and honest and responsible behavior. Supporting factors include a religious school environment, teacher-parent collaboration, and availability of religious facilities. Inhibiting factors are differences in family backgrounds and limited learning time.